G-quadruplex structure of the C. elegans telomeric repeat: a two tetrads basket type conformation stabilized by a non-canonical C–T base-pair. Issue 12 (23rd June 2022) - Marquevielle, Julien; De Rache, Aurore; Vialet, Brune; Morvan, Estelle; Mergny, Jean-Louis; Amrane, Samir
Abstract: The Caenorhabditis elegans model has greatly contributed to the understanding of the role of G-quadruplexes in genomic instability. The GGCTTA repeats of the C. elegans telomeres resemble the GGGTTA repeats of the human telomeres. However, the comparison of telomeric sequences ( Homo sapiens, Tetrahymena, Oxytricha, Bombyx mori and Giardia ) revealed that small changes in these repeats can drastically change the topology of the folded G-quadruplex. In the present work we determined the structure adopted by the C. elegans telomeric sequence d[GG(CTTAGG)3 ]. The investigated C. elegans telomeric sequence is shown to fold into an intramolecular two G-tetrads basket type G-quadruplex structure that includes a C–T base pair in the diagonal loop. This work sheds light on the telomeric structure of the widely used C. elegans animal model. Graphical Abstract: